Construction of Phthalocyanine-Titanium Dioxide/Graphene/Polyaniline Composite Electrodes by Electrochemical Method for Supercapacitor Applications - Arvas, Melih Besir; Artar, Emirhan; Gorduk, Ozge; Gorduk, Semih; Sahin, Yucel (ELECTROCHEMICAL SOC INC, 2023)
Supercapacitors (SCs) are the most interesting alternative energy storage and conversion systems to successfully overcome the global energy problem for future generations. A lot of work has been done to improve the capacitive performance of an electrode and to achieve high power and energy density. Herein, for the first time in the literature, we prepared hybrid composite materials consisting of metallo phthalocyanine doped-titanium dioxide (MPc-TiO2) and high conductivity graphene (Gr) and polyaniline (PANI) in a one-step on pencil graphite electrode (PGE) using the cyclic voltammetry method. The microscopic and structural characteristics of the synthesized MPc-TiO2/Gr/PANI/PGE (M=Cu and Co) are analyzed by various spectroscopic and analytical techniques. As a result, the optimized CoPc-TiO2/Gr/PANI/PGE as the electrode shows a highly specific capacitance of 401.5 F g(-1) at 5 A g(-1) and excellent cyclic stability up to 1000 cycles. The good electrochemical performance could be attributed to the synergistic effect of the high pseudocapacitance and good conductivity of CoPc-TiO2 as well as the capacitive contribution and conductivity of Gr and PANI. Our strategy provides a new avenue to develop high-performance SCs via rational integration of MPc-TiO2 with Gr and PANI.
Keywords: REDUCED GRAPHENE OXIDE; POLYANILINE/GRAPHENE NANOCOMPOSITES; METAL-OXIDES; PERFORMANCE; HYDROGEL; DEVICES; Materials Science; Physics